Diets, fruit and vegetables consumption, and nutritional status in Benin: A scoping review - Bliznashka, Lilia; Pather, Kamara; Mitchodigni, Irene M.; Hess, Sonja Y.; Olney, Deanna K. (Wiley, 2026)
Unhealthy diets, including low fruit and vegetables (F&V) intake, contribute to morbidity and mortality related to non-communicable diseases. Designing culturally appropriate interventions to improve diets and F&V intake requires an in-depth understanding of individual-level dietary patterns, household consumption patterns, and nutritional status resulting from inadequate F&V intake. In this scoping review, we summarised the literature on diets, F&V intake, and nutritional status in Benin. We searched PubMed from 2012 to August 2024 to identify articles on diets and nutritional status, and from 2002 to August 2024 to identify articles on F&V intake. We included 36 articles on diets, 27 on F&V intake, and 16 on nutritional status. Existing literature demonstrated that Beninese diets are cereal-based and monotonous, characterised by low diversity and low F&V intake across all population groups. Available evidence indicated a high burden of undernutrition in children <5 years of age, a rising prevalence of overnutrition in women of reproductive age, and a high prevalence of overnutrition in adults. Evidence on how diets and F&V intake vary by urban/rural location, season, and socioeconomic characteristics was limited and inconsistent. Two evaluations of garden irrigation programmes assessed impacts on women's dietary diversity and F&V consumption. Additional research is needed to improve our understanding of diets, F&V intake, and diet-related nutritional challenges and how they evolve over time and across different population groups. Understanding these gaps can help identify entry points and targets for interventions to improve diet quality and F&V intake in Benin.